A rare HCN4 variant combined with sick sinus syndrome, left ventricular noncompaction, and complex congenital heart disease - Fengxiao Zhang; Ning Zhao; Lin Wang; Hua Peng; Ying Jiang; Min Cheng; Feng Zhu (Channels)
The hyperpolarization-activated cyclic nucleotide-gated potassium channel 4 (HCN4) gene has been reported to regulate the spontaneous depolarization of sinoatrial node cells. A novel HCN4 mutation (c.2036 G>A) may lead to sick sinus syndrome. The green fluorescent protein (GFP) and either the wild-type (WT) or C679Y mutant (mut) were co-transfected into HEK293 cells to investigate the impact of the mutation on HCN4 channel function. The whole-cell patch-clamp approach was utilized to record HCN4 currents. According to electrophysiological recording, the current amplitude and density generated by mut-C679Y HCN4 channels were much lower than those generated by WT channels. HCN4 channel current activation was not significantly affected by the C679Y mutation. Because of the little current, analyzing the mut channel deactivation kinetic was challenging. Thus, we have identified a novel HCN4 gene mutation that is connected to bradycardia, left ventricular noncompaction, and diverse valve-related heart conditions.